If objects could talk: a novel resource discovery approach for pervasive environments. (10th December 2007) - Ruta, Michele; Di Noia, Tommaso; Di Sciascio, Eugenio; Scioscia, Floriano, Giacomo Piscitelli
We propose to extend standard Radio Frequency IDentification (RFID) usage by storing semantically annotated data within RFID tags memory, so that objects may actually 'describe themselves' in a variety of scenarios. In particular here we exploit our approach to carry out an advanced matchmaking process using metadata stored in RFIDs. A 'fully backward compatible' modification to the original RFID data exchange protocol is presented, allowing to implement an advanced resource discovery framework. A compression algorithm specifically devised to ease embedding of annotated DIG description is also proposed. Motivations and benefits of the approach are outlined in a tracking of agricultural and food products case study.